Manufacturing method of printed matter
The method of applying electron-curing ink on a polyamide film with a polyurethane layer and irradiation enhances adhesion, addressing the issue of ink detachment during boiling and sterilization in active energy ray-curing inks.
Patent Information
- Application Number
- JP2020545204
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-27
- Filing Date
- 2020-08-18
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-08-18
AI Technical Summary
Existing active energy ray-curing inks used for printing on films, particularly food wrapping films, suffer from insufficient adhesion, which further deteriorates during boiling and retort sterilization processes.
A manufacturing method involving the application of an electron-curing type ink on a polyamide film layer containing a polyurethane layer with a polyol component, followed by irradiation with a 30 kGy electron beam to enhance adhesion, using a waterless flat printing process.
Maintains strong adhesion between the ink and film after boiling and retort sterilization, ensuring durable printed matter.
Smart Images

Figure 0007625861000003 
Figure 0007625861000001 
Figure 0007625861000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a printed matter. [Background technology]
[0002] In recent years, the use of active energy ray-curable printing inks, which can instantly cure inks by irradiating them with active energy rays such as ultraviolet rays, has spread in many fields due to their advantages in terms of equipment, safety, the environment, and productivity. In addition, since a large amount of petroleum-based solvents are used as cleaning agents for inks used in printing processes, active energy ray-curable lithographic printing inks have been disclosed that can use cleaning agents mainly composed of water that does not contain volatile solvents.
[0003] Since active energy ray-curable printing inks can be cured at room temperature in a short time, they are considered to be the most suitable materials for forming films on plastic substrates with poor heat resistance. However, when active energy ray-curable printing inks are used to print on films, the adhesion between the ink and the film can be insufficient.
[0004] For this reason, active energy ray-curable printing inks with excellent adhesion to films have been developed (see, for example, Patent Document 1). In addition, techniques have been developed to improve adhesion between the ink and the film by modifying the film surface (see, for example, Patent Documents 2 and 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-168730 A [Patent Document 2] JP 2011-94125 A [Patent Document 3] International Publication No. 2018 / 163941 Summary of the Invention [Problem to be solved by the invention]
[0006] However, even when these techniques are used, the adhesion between the ink and the film can be insufficient. In particular, when printing on food packaging film, the adhesion between the ink and the film can be significantly reduced when the film on which the ink is printed is boiled for boiling sterilization or retort sterilization.
[0007] Therefore, an object of the present invention is to provide a method for producing a printed matter in which the adhesion between the ink and the film is good even after boiling treatment such as boiling sterilization or retort sterilization. [Means for solving the problem]
[0008] The present invention relates to a method for producing a printed matter, comprising the steps of printing an electron beam curable ink on a film and irradiating the surface on which the ink is printed with an electron beam, the method comprising the steps of: printing an electron beam curable ink on a film; and irradiating the surface on which the ink is printed with an electron beam. The method comprises the steps of: printing an electron beam curable ink on a film; and irradiating the surface on which the ink is printed with an electron beam. The method comprises the steps of: printing an electron beam curable ink on a film; Rura The amount of calcium is 2 x 10 18 the ink is printed on a layer containing a polyurethane in which the polycarbonate polyol is used as a polyol component, and the method for producing a printed matter is also provided. Effect of the Invention
[0009] According to the method for producing a printed matter of the present invention, good adhesion between the ink and the film can be maintained even after a boiling treatment such as boiling sterilization or retort sterilization. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a side view showing an example of a method for producing a printed matter according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] A preferred embodiment of the method for producing a printed matter according to the present invention will be described in detail below. However, the present invention should not be interpreted as being limited to the following exemplary embodiment, and various modifications can be made according to the purpose and application without departing from the gist of the present invention.
[0012] The method for producing a printed matter according to an embodiment of the present invention includes printing ink onto a film, and then irradiating the surface onto which the ink has been applied with active energy rays. The film is characterized in that it includes a polyamide film layer (hereinafter, this layer may be referred to as a "polyamide base layer") and a layer containing polyurethane in which polycarbonate polyol is used as a polyol component, as the outermost layer on at least one surface.
[0013] A specific embodiment of the method for producing such a printed matter is as follows: First, an ink film is obtained on the film surface by a step of applying ink onto the film, and then, the ink film thus obtained on the film is irradiated with active energy rays to cure the ink and obtain a printed matter.
[0014] Methods for applying ink onto a film include well-known methods such as flexographic printing, lithographic printing, gravure printing, screen printing, bar coater, etc. In particular, lithographic printing is preferably used because it allows the ink to be applied to the substrate at high speed and enables large-volume printing at low cost.
[0015] Planographic printing includes a method using a waterless planographic printing plate and a method using a water-containing planographic printing plate. In the method for producing a printed matter of the present invention, it is preferable to use a waterless planographic printing plate. In the method using a waterless planographic printing plate, since no dampening water is used during printing, radicals can be stably generated when the ink is irradiated with active energy rays. Therefore, the ink can be sufficiently cured and the adhesion between the ink and the film can be sufficiently maintained.
[0016] The thickness of the ink on the printed matter is preferably 0.1 to 50 μm. By having the ink thickness in the above range, it is possible to reduce the ink cost while maintaining good printing quality without reducing the adhesion between the ink and the film.
[0017] Next, an example of a method for producing a printed matter according to an embodiment of the present invention when a waterless lithographic printing plate is used will be described with reference to Fig. 1. Note that, although an example using a blanket 4 will be described below, the present invention is not limited thereto, and it is also possible to apply active energy ray curable ink directly from an ink roller 1 to the surface of a lithographic printing plate 2 mounted on a plate cylinder 3 without using a blanket 4, and then directly transfer the ink to a lithographic printing substrate. Also, an example in which the ink is supplied from above a film 5 will be described below, but the ink may also be supplied from below the film 5. Note that a mechanism for irradiating active energy rays is not shown in Fig. 1.
[0018] First, the lithographic printing plate 2 is mounted on the plate cylinder 3. The lithographic printing plate 2 has an ink-repellent layer and a heat-sensitive layer (not shown) on its surface in a desired pattern.
[0019] Next, ink is supplied to the ink roller 1. The ink supplied to the ink roller 1 adheres to the surface of the heat-sensitive layer on the surface of the lithographic printing plate 2 mounted on the plate cylinder 3. The ink does not adhere to the ink-repellent layer.
[0020] The ink adhering to the surface of the heat-sensitive layer of the lithographic printing plate 2 is transferred to the surface of the blanket 4 at the point of contact with the blanket 4. The ink adhering to the blanket 4 is transferred to the film 5 arranged on the support roller 6 at the point of contact with the film 5.
[0021] Then, the film 5 is irradiated with active energy rays to cure the ink, thereby obtaining a printed matter. The active energy rays are not particularly limited as long as they have the excitation energy required for the curing reaction of the ink, and for example, ultraviolet rays and electron beams are preferably used. In particular, electron beams are preferably used to increase the adhesion between the film and the ink.
[0022] When curing with ultraviolet light, ultraviolet irradiation devices such as high-pressure mercury lamps, xenon lamps, metal halide lamps, and light-emitting diodes are preferably used. The use of light-emitting diodes that emit an emission line with a wavelength of 350 to 420 nm is preferable from the viewpoints of suppressing heat generation, saving power, and reducing costs. For example, when a light-emitting diode that emits an emission line with a wavelength of 385 nm is used, the irradiation intensity is 5 to 20 mW / cm. 2 From the viewpoint of productivity, it is preferable to carry out curing using a light emitting diode having an illuminance of 50 to 150 m / min on a conveyor.
[0023] When curing with electron beams, an electron beam device having an energy beam of 100 to 500 keV is preferably used. A feature of curing with electron beams is that even if the ink contains a coloring material such as a pigment, the ink can be easily cured to the inside because the transparency is not easily reduced. A film dosimeter is used to measure the amount of electron beams, and a radiochromic dosimeter is preferably used.
[0024] In the present invention, the amount of electron beam required to cure the ink with an electron beam depends on the ink film thickness and pigment density, but is preferably 5 kGy to 100 kGy, more preferably 10 kGy to 50 kGy, and even more preferably 15 to 30 kGy.
[0025] In the above-exemplified production method, the rotation speed of each roller is not particularly limited, and can be set appropriately depending on the quality required for the printed matter, the takt time, and the properties of the ink.
[0026] After printing, the ink remaining on the ink roller 1, the lithographic printing plate 2, and the blanket 4 can be easily removed with water or an aqueous solution whose main component is water.
[0027] (film) In the present invention, a film is used that includes a polyamide substrate layer and a layer containing polyurethane in which polycarbonate polyol is used as a polyol component as the outermost layer on at least one side (hereinafter, this layer may be referred to as an "easy adhesion layer"). Usually, polyurethane is synthesized from polyisocyanate and polyol as raw materials, but the characteristics related to heat resistance and water resistance change significantly, especially by changing the type of polyol. In the present invention, the heat resistance and water resistance of polyurethane can be improved by using polycarbonate polyol as the polyol. By using such a layer containing polyurethane as the outermost layer of the film, the adhesion between the ink and the film to which the ink is applied can be maintained well even after boiling treatment for boiling sterilization or retort sterilization.
[0028] As polyols, diols having two hydroxyl groups and triols having three hydroxyl groups are well known, and either of them can be suitably used in the present invention. Therefore, both polycarbonate diols and polycarbonate triols are preferably used, but polycarbonate diols are more suitably used from the viewpoints of production volume and cost.
[0029] The polycarbonate diol can be synthesized by carrying out an ester exchange reaction using a dihydroxy compound and a carbonate compound as raw material monomers.
[0030] Examples of dihydroxy compounds include 2,2-dialkyl-substituted 1,3-propanediols such as 2,2-dimethyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, and 2-pentyl-2-propyl-1,3-propanediol, tetraalkyl-substituted alkylenediols such as 2,2,4,4-tetramethyl-1,5-pentanediol and 2,2,9,9-tetramethyl-1,10-decanediol, 3,9-bis(1,1-dimethyl-2-hydrogen)diol, and tetraalkyl-substituted alkylenediols such as 2,2,4,4-tetramethyl-1,5-pentanediol and 2,2,9,9-tetramethyl-1,10-decanediol, tetraalkyl-substituted alkylenediols such as 3,9-bis(1,1-dimethyl-2-hydrogen)diol, and tetraalkyl-substituted alkylenediols such as 3,9-bis(1,1-dimethyl-2-hydrogen)diol. Examples of such cyclic group-containing diols include 2,2-diphenyl-1,3-propanediol, 2,2-divinyl-1,3-propanediol, 2,2-diethynyl-1,3-propanediol, 2,2-dimethoxy-1,3-propanediol, bis(2-hydroxy-1,1-dimethylethyl)ether, bis(2-hydroxy-1,1-dimethylethyl)thioether, and 2,2,4,4-tetramethyl-3-cyano-1,5-pentanediol.
[0031] The carbonate compound is not limited as long as it does not impair the effects of the present invention, and may be a dialkyl carbonate, a diaryl carbonate, or an alkylene carbonate. Specific examples include dimethyl carbonate, diethyl carbonate, dibutyl carbonate, diphenyl carbonate, ethylene carbonate, hexamethylene carbonate, etc., and alkylene carbonates such as ethylene carbonate and hexamethylene carbonate are preferred from the viewpoint of high flexibility and improved adhesion.
[0032] Regarding polyisocyanates, diisocyanates having two isocyanate groups in one molecule are generally used. Specific examples thereof include aromatic isocyanates such as 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate (TDI), 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 2,4-diphenylmethane diisocyanate, and 1,5-naphthylene diisocyanate, as well as ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), and dodecamethylene diisocyanate. Examples of the isocyanate include, but are not limited to, aliphatic isocyanates such as diisocyanate, 1,6,11-undecane triisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and lysine diisocyanate, and alicyclic isocyanates such as isophorone diisocyanate (IPDI), 4,4'-dicyclohexylmethane diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, and methylcyclohexylene diisocyanate (hydrogenated TDI).
[0033] In the present invention, as described above, the outermost layer is a layer containing polyurethane in which polycarbonate polyol is used as a polyol component, and it is preferable that the polyurethane used in the layer is substantially not copolymerized with other polymer species. The meaning of "substantially" here is that the content of repeating units of other polymer species, such as acrylic acid alkyl ester units and methacrylic acid alkyl ester units, in the molecule is 5 mol % or less, preferably 1 mol or less.
[0034] In the present invention, a film may be used in which a layer containing polyurethane (easy adhesion layer) as described above is previously provided on the surface of a substrate film, or a layer containing polyurethane as described above may be later formed on the surface of a substrate film by a coating method or the like.
[0035] The method for forming the easy-adhesion layer is not particularly limited, but it is preferable to use a coating method. Specifically, there is a method for forming the easy-adhesion layer in a process separate from the manufacturing process of the substrate, which is called an off-line coating method, and a method for coating during the manufacturing process, which is called an in-line coating method.
[0036] Off-line coating methods include roll coating, dip coating, bar coating, die coating, and gravure coating, and a combination of these methods can also be used.
[0037] From the viewpoint of production cost and thickness uniformity, an in-line coating method is preferably used. In the case of the in-line coating method, coating is performed at any stage from melt extrusion of the resin to be the substrate to winding up, and usually, coating is performed on any of the substrates: an unstretched (unoriented) substrate (A) in a substantially amorphous state obtained by melt extrusion and quenching, a uniaxially stretched (uniaxially oriented) substrate (B) which is then stretched in the longitudinal direction, or a biaxially stretched (biaxially oriented) substrate (C) which is further stretched in the transverse direction and has not yet been heat-treated.
[0038] A known method can be used as the coating method, and examples thereof include reverse coating, spray coating, bar coating, gravure coating, rod coating, and die coating. It is preferable to adopt a method in which a coating liquid is applied to the substrate (A) or (B) before the crystal orientation is completed, and then the substrate coated with the coating liquid is stretched in a uniaxial or biaxial direction and heat-treated at a temperature higher than the boiling point of the solvent to complete the crystal orientation of the resin to be the substrate and provide an easy-adhesion layer. According to this method, the film formation of the substrate and the coating and drying of the coating liquid can be performed simultaneously, which is advantageous in terms of production costs. In addition, the thickness of the easy-adhesion layer can be easily made thinner by performing stretching after coating. Among them, a method in which a coating liquid is applied to a substrate (B) uniaxially stretched in the longitudinal direction, and then the substrate is stretched in the width direction and heat-treated is excellent.
[0039] In the present invention, the thickness of the film on which the ink is printed is preferably 5 μm or more and 200 μm or less, and more preferably 10 μm or more and 30 μm or less.
[0040] In the present invention, when the film on which the ink is printed is irradiated with an electron beam of 30 kGy (kilogray) from the surface on which the easy-adhesion layer is provided, the amount of radicals present on the surface layer of the film is 2×10 per 1 g of the film. 18 10 or more, i.e., 2×10 18 The amount of radicals per square centimeter of the film is preferably 1 / g or more. 2 3.4 x 10 per 15 3.4×10 or more 15 pieces / cm 2 It is preferable that the absorbed dose of the electron beam is equal to or more than this. The absorbed dose of the electron beam is expressed in units of kGy (kilogray), and 1 kGy indicates that 1 joule of energy is absorbed per 1 kg of the irradiated material. When the surface layer of the film is irradiated with an electron beam, radicals are generated in the ink, which results in the ink curing. However, since the electron beam that penetrates the ink also acts on the surface layer of the film, radicals are also generated from other components of the surface layer of the film, that is, the easy-adhesion layer and the polyamide base layer present near the surface. The more radicals present on the surface layer of the film, the easier the crosslinking reaction will proceed between the ink and the surface layer of the film, and therefore it is considered that the adhesion between the printed matter (the cured ink) and the surface layer of the film will be higher.
[0041] The amount of radicals present on the surface of a film when the surface of the film is irradiated with an electron beam can be measured using an electron spin resonance (ESR) device. The amount of free radicals present on the surface of the film after irradiation with 30 kGy of electron beam is the amount of the radicals.
[0042] In order to set the amount of radicals generated when the surface layer of the film is irradiated with an electron beam within the above range, the substrate may be a polyethylene film, a polypropylene film, a polyamide film, etc., but in the present invention, a polyamide film is used, which is easy to coat. Polyamide films are excellent in physical strength such as tensile strength, impact strength, and pinhole strength, and in heat resistance.
[0043] In the present invention, examples of materials that can be used for the polyamide substrate layer include "Bonyl Q" manufactured by Kohjin Film Co., Ltd.
[0044] In the measurement from the surface on the side where the easy-adhesion layer is provided, the ratio of the peak intensity v1 of the stretching vibration of the carbon-nitrogen single bond to the peak intensity v2 of the stretching vibration of the carbon-oxygen double bond, v1 / v2, determined by the FT-IR-ATR method, is preferably within the range of 0.5 to 1. (Hereinafter, the ratio of the peak intensity v1 of the stretching vibration of the carbon-nitrogen single bond to the peak intensity v2 of the stretching vibration of the carbon-oxygen double bond will be simply represented as v1 / v2.) The peak intensity v1 of the stretching vibration of the carbon-nitrogen single bond is about 1530 cm -1 The peak intensity ν2 of the stretching vibration of the carbon-oxygen double bond is approximately 1740 cm -1 It can be expressed as the area of the peak appearing at a wave number in the vicinity. When a peak originating from the polyamide base layer is observed, the peak is excluded from the calculation of v1 / v2.
[0045] The peak intensity v1 of the stretching vibration of the carbon-nitrogen single bond is considered to reflect the amount of urethane bonds present, and the peak intensity v2 of the stretching vibration of the carbon-oxygen double bond is considered to reflect the amount of carbonate bonds present due to polyol. That is, when v1 / v2 is 0.5 or more, the proportion of urethane bonds is sufficient, and therefore good adhesion between the ink and the film can be maintained. On the other hand, when v1 / v2 is 1 or less, the proportion of the polyol component is sufficient, and therefore an easy-adhesion layer with high flexibility and good heat resistance can be obtained.
[0046] As the electron beam irradiation device, a conventionally known device can be used, and for example, a curtain type electron beam irradiation device or a line irradiation type low energy electron beam irradiation device can be suitably used.
[0047] In the present invention, the surface roughness Ra of the surface on which the easy-adhesion layer is provided is preferably 5 to 30 nm. By making Ra 5 nm or more, an anchor effect occurs at the ink interface, so that the adhesive strength with the ink can be increased. Also, by making Ra 30 nm or less, wetting of the ink is not hindered.
[0048] The surface roughness Ra can be measured, for example, using an atomic force microscope (AFM) or the like based on the method described in JIS R 1683:2007.
[0049] In order to set Ra in the above range, for example, it is preferable to include fine particles having an average particle diameter D50 of about 10 to 20 nm in the easy-adhesion layer. The content of the fine particles in the easy-adhesion layer is not particularly limited, but is preferably 0.1 to 10 parts by mass per 100 parts by mass of polyurethane. The average particle diameter D50 refers to the particle diameter when the cumulative passing amount from the small particle side is 50% in the volume-based particle size distribution obtained by measuring by dynamic light scattering. As the fine particles, silica particles, alumina particles, etc. are preferably used in terms of dispersibility, stability, and cost.
[0050] (Ink) The ink used in the present invention is preferably one that is cured by active energy rays. By irradiating the ink with active energy rays, the ink on the printed matter can be cured. When the ink is cured with active energy rays, generally, internal stress due to cure shrinkage is likely to occur, which is a factor in reducing the adhesion between the ink and the film. However, by using the above-mentioned film as the film to be printed, the adhesion between the ink and the film can be maintained good.
[0051] One embodiment of the ink used in the present invention is an active energy ray curable printing ink, and the resin contained in the ink is preferably an acrylic resin having an acid value of (a) 30 mgKOH / g to 250 mgKOH / g. The acid value is more preferably 60 mgKOH / g to 200 mgKOH / g, and particularly preferably 75 mgKOH / g to 150 mgKOH / g. When the acid value is within the above range, the sensitivity of the ink curing reaction by active energy rays is increased, and a good ink cured film can be obtained even with low energy irradiation, and high water resistance can be achieved. The acid value can be determined in accordance with the neutralization titration method in Section 3.1 of the test method of JIS K 0070:1992.
[0052] The acrylic resin preferably has an ethylenically unsaturated group, which not only provides high sensitivity for active energy ray curing, but also provides the cured film with excellent water resistance.
[0053] In addition, by having an ethylenically unsaturated group in the side chain, the resin having the ethylenically unsaturated group itself has the ability to be cured by active energy rays. Therefore, the ink is cured by a radical reaction between high molecular weight resins when irradiated with active energy rays, so the amount of exposure to active energy rays required for curing is small, resulting in high sensitivity to active energy rays.
[0054] This means that, for example, even in UV printing, where ink is instantly cured by irradiating it with ultraviolet light as active energy rays, sufficient ink curing can be achieved with a small amount of UV radiation. This makes it possible to significantly improve productivity by increasing printing speed, and reduce costs by using energy-saving UV light sources (for example, metal halide lamps and LEDs).
[0055] Furthermore, the acrylic resin contains an ethylenically unsaturated group and has a suitable acid value, so that the adhesion between the ink using the acrylic resin and the film is excellent. This is believed to be because the surface layer of the film is a layer containing polyurethane containing polycarbonate polyol as a diol component, and therefore bonds are formed between the carboxyl group contained in the resin in the ink and the amino group, etc. present on the film surface.
[0056] In addition, the ink used in the present invention may preferably contain a resin other than the acrylic resin, which has an ethylenically unsaturated group and a carboxyl group. Ink containing such a resin has high sensitivity to active energy ray curing, and the cured film has excellent water resistance. In addition, the acid value of the resin other than the acrylic resin is preferably 30 mgKOH / g or more and 250 mgKOH / g or less. Examples of such resins include styrene-maleic acid resin, rosin-modified maleic acid resin, epoxy resin, polyester resin, polyurethane resin, and phenolic resin.
[0057] The weight average molecular weight of the acrylic resin and the resin other than the acrylic resin, which has an ethylenically unsaturated group and a carboxyl group, is preferably 5,000 or more, more preferably 15,000 or more, and even more preferably 20,000 or more in order to obtain the water resistance of the cured film. Also, in order to obtain the water solubility of the resin, it is preferably 100,000 or less, more preferably 75,000 or less, and even more preferably 50,000 or less. In this specification, the weight average molecular weight can be obtained by measuring using gel permeation chromatography (GPC) in terms of polystyrene.
[0058] The content of the acrylic resin and the resin other than the acrylic resin, which has an ethylenically unsaturated group and a carboxyl group, contained in the ink used in the present invention is preferably 5% by mass or more, more preferably 10% by mass or more, in order to obtain the ink viscosity required for printing and the sensitivity required for curing, and is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less, in order to obtain the ink fluidity and transferability between rollers required for printing.
[0059] The ink used in the present invention preferably contains (b) a pigment, and (c) a (meth)acrylate having a hydroxyl group.
[0060] As the (b) pigment, it is preferable to use at least one type selected from inorganic pigments and organic pigments.
[0061] Specific examples of inorganic pigments used in the present invention include titanium oxide, zinc oxide, calcium carbonate, barium sulfate, red iron oxide, cadmium red, yellow lead, zinc yellow, iron blue, ultramarine, organic bentonite, alumina white, iron oxide, carbon black, graphite, and aluminum.
[0062] Specific examples of organic pigments include phthalocyanine pigments, soluble azo pigments, insoluble azo pigments, lake pigments, quinacridone pigments, isoindoline pigments, threne pigments, and metal complex pigments, and specific examples thereof include phthalocyanine blue, phthalocyanine green, azo red, monoazo red, monoazo yellow, disazo red, disazo yellow, quinacridone red, quinacridone magenta, and isoindoline yellow.
[0063] These pigments (b) can be used alone or in combination of two or more kinds.
[0064] The amount of the pigment (b) contained in the ink used in the present invention is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on 100% by mass of the ink, in order to obtain a sufficient printing surface density. Also, in order to improve the fluidity of the ink and obtain good inter-roller transferability, the amount is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, based on 100% by mass of the ink.
[0065] In addition, the use of (c) a (meth)acrylate having a hydroxyl group improves the fluidity of the ink and makes it possible to adjust the ink properties such as viscosity and leveling ability, since the hydroxyl group has the effect of dispersing and stabilizing the pigment. In addition, since the ink is cured by irradiation with active energy rays, the water resistance of the cured film can be improved.
[0066] (c) The hydroxyl value of the (meth)acrylate having a hydroxyl group is preferably 50 mgKOH / g or more, since this improves the pigment dispersibility. More preferably, it is 75 mgKOH / g or more, and even more preferably, it is 100 mgKOH / g or more. In addition, the hydroxyl value is preferably 200 mgKOH / g or less, since this allows the ink to have good fluidity. More preferably, it is 180 mgKOH / g or less, and even more preferably, it is 160 mgKOH / g or less.
[0067] Specific examples of (c) hydroxyl group-containing (meth)acrylates include poly(meth)acrylates of polyhydric alcohols such as trimethylolpropane, glycerin, pentaerythritol, diglycerin, ditrimethylolpropane, isocyanuric acid, and dipentaerythritol, and their alkylene oxide adducts. More specific examples include di(meth)acrylate of trimethylolpropane, di(meth)acrylate of glycerin, di- or tri(meth)acrylate of pentaerythritol, di- or tri(meth)acrylate of diglycerin, di- or tri(meth)acrylate of ditrimethylolpropane, di-, tri-, tetra-, or penta(meth)acrylate of dipentaerythritol, and their ethylene oxide adducts, propylene oxide adducts, and tetraethylene oxide adducts. Also usable is a (meth)acrylate obtained by reacting a compound having a plurality of hydroxyl groups and a carboxyl group with glycidyl (meth)acrylate. Examples of the compound having a plurality of hydroxyl groups and a carboxyl group include bisphenol A, hydrogenated bisphenol A, bisphenol F, and hydrogenated bisphenol F. More specifically, examples include di(meth)acrylate of bisphenol A, di(meth)acrylate of bisphenol F, di(meth)acrylate of hydrogenated bisphenol A, di(meth)acrylate of hydrogenated bisphenol F, and their ethylene oxide adducts, propylene oxide adducts, and tetraethylene oxide adducts. Among the above, pentaerythritol tri(meth)acrylate, diglycerin tri(meth)acrylate, and ditrimethylolpropane tri(meth)acrylate are particularly preferred because they have excellent pigment dispersibility and improved background smear resistance.
[0068] The content of (c) the (meth)acrylate having a hydroxyl group is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on 100% by mass of the ink, in order to obtain an ink viscosity suitable for printing. Also, the content is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less, in order to obtain a cured film having good sensitivity and sufficient water resistance.
[0069] The ink used in the present invention preferably further contains (d) a bifunctional (meth)acrylate having a chain aliphatic skeleton with 8 to 18 carbon atoms (hereinafter referred to as "(d) aliphatic bifunctional (meth)acrylate"). However, among (d) aliphatic bifunctional (meth)acrylates, those having a hydroxyl group are classified as (c) (meth)acrylates having a hydroxyl group. It is preferable that the (d) aliphatic bifunctional (meth)acrylate has a hydroxyl value of 5 mgKOH / g or less and exhibits hydrophobicity. The chain aliphatic skeleton of the (d) aliphatic bifunctional (meth)acrylate may be either a straight chain skeleton or a branched skeleton, and may have either a saturated bond or an unsaturated bond. The hydrophobic (d) aliphatic bifunctional (meth)acrylate has a moderate compatibility with the (b) resin having an ethylenically unsaturated group and a carboxyl group, and the (c) (meth)acrylate having a hydroxyl group, and suppresses the entanglement of the molecular chains in the ink, suppressing the spinnability when the ink is transferred, improving the ink transferability. In addition, the ink used in the present invention contains the hydrophobic (d) aliphatic bifunctional (meth)acrylate, which reduces the surface tension of the ink and improves the wettability of the ink to the substrate, improving the ink transferability and adhesion to the substrate. Here, the ink transferability refers to the transfer rate when the ink is transferred from the rubber (metal) roller to the rubber (metal) roller, from the rubber (metal) roller to the plate, from the plate to the blanket, and from the blanket to the substrate.
[0070] In order to maintain a suitable compatibility with (b) the resin having an ethylenically unsaturated group and a carboxyl group, and (c) the (meth)acrylate having a hydroxyl group, and to improve ink transferability, the carbon number of (d) the aliphatic bifunctional (meth)acrylate is preferably 8 or more, more preferably 9 or more, and even more preferably 10 or more. In order to suppress deterioration of compatibility with (b) the resin having an ethylenically unsaturated group and a carboxyl group, and (c) the (meth)acrylate having a hydroxyl group, an increase in the viscosity of the ink, and deterioration of ink transferability, the carbon number of (d) the aliphatic bifunctional (meth)acrylate is preferably 18 or less, more preferably 16 or less, and even more preferably 14 or less.
[0071] In order to maintain a suitable level of compatibility and improve ink transferability, the content of the (d) aliphatic bifunctional (meth)acrylate in the ink is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on the total mass of the ink. For the same reasons, the content of the (d) aliphatic bifunctional (meth)acrylate is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, and even more preferably 8% by mass or less, based on 100% by mass of the ink used in the present invention.
[0072] Specific examples of (d) aliphatic bifunctional (meth)acrylates include 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,11-undecanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, 1,13-tridecanediol di(meth)acrylate, and 1,14-tetradecanediol di(meth)acrylate. Examples of the di(meth)acrylate include 1,15-pentadecanediol di(meth)acrylate, 1,16-hexadecanediol di(meth)acrylate, 1,17-heptadecanediol di(meth)acrylate, 1,18-octadecanediol di(meth)acrylate, 4-methyl-1,10-decanediol di(meth)acrylate, and 4-ethyl-1,10-decanediol di(meth)acrylate. The di(meth)acrylate may also be a polyester di(meth)acrylate having an aliphatic skeleton having 8 to 18 carbon atoms as a repeating unit. The di(meth)acrylate may also contain two or more of these. Among the above, 1,10-decanediol di(meth)acrylate is particularly preferred in order to maintain compatibility with (b) a resin having an ethylenically unsaturated group and a carboxyl group, and (c) a (meth)acrylate having a hydroxyl group to an appropriate degree, and to improve ink transferability. The functionality herein refers to the number of structures derived from (meth)acrylate.
[0073] (d) The weight average molecular weight of the aliphatic bifunctional (meth)acrylate is preferably 100 or more, more preferably 150 or more, and even more preferably 200 or more, in order to soften the ink film and provide adhesion to the substrate. Also, in order to maintain the viscosity of the ink and improve its fluidity, the weight average molecular weight is preferably 1,000 or less, more preferably 700 or less, and even more preferably 500 or less. When the chemical structure is known, the weight average molecular weight is the molecular weight of the compound itself, and when the compound has a molecular weight distribution, the weight average molecular weight can be obtained by measuring the molecular weight in terms of polystyrene using gel permeation chromatography (GPC).
[0074] The ratio of the (d) aliphatic bifunctional (meth)acrylate based on the total amount of the (b) resin having an ethylenically unsaturated group and a carboxyl group (1.00 part by mass) is preferably 0.10 parts by mass or more, more preferably 0.15 parts by mass or more, and even more preferably 0.20 parts by mass or more, in order to maintain a suitable compatibility with the resin (a) and improve ink transferability. For the same reason, the ratio of the (d) aliphatic bifunctional (meth)acrylate based on the total amount of the (b) resin having an ethylenically unsaturated group and a carboxyl group (1.00 part by mass) is preferably 0.60 parts by mass or less, more preferably 0.45 parts by mass or less, and even more preferably 0.30 parts by mass or less.
[0075] The ink used in the present invention preferably further contains (e) a urethane (meth)acrylate.
[0076] The hydrogen bonds between the urethane bonds contained in the (e) urethane (meth)acrylate form hard segments that can impart toughness to the ink film, and can also provide good adhesion by forming strong bonds with the surface of a plastic film, etc. In particular, since the molecular structural characteristics of the ink are similar to those of the easy-adhesion layer of the film surface of the present invention, the ink can have high affinity with the easy-adhesion layer, thereby obtaining extremely good adhesion. In addition, the (e) urethane (meth)acrylate contains a polyol, and thus forms soft segments that can impart flexibility to the ink film.
[0077] (e) The urethane (meth)acrylate preferably has at least one of an ester structure and a polycarbonate structure. When the urethane (meth)acrylate has at least one of an ester structure and a polycarbonate structure, the heat resistance and coating film properties of the ink can be effectively improved by these rigid structures. In addition, these rigid structures suppress entanglement of the molecular chains formed, keep the ink viscosity low, and improve the ink fluidity, thereby obtaining good transferability during printing.
[0078] The alcohol that gives the ester structure is preferably a polyhydric alcohol, and the dicarboxylic acid that gives the ester structure is not particularly limited, but includes phthalic acid, isophthalic acid, terephthalic acid, adipic acid, oxalic acid, maleic acid, fumaric acid, sebacic acid, etc. Among these, isophthalic acid and adipic acid are particularly preferred because they are relatively inexpensive, have good heat resistance, and maintain good compatibility with ink.
[0079] Examples of carbonate polyols that give urethane having a carbonate structure include pentamethylene carbonate diol, hexamethylene carbonate diol, hexane carbonate diol, and decane carbonate diol. However, due to the high cohesive strength of the carbonate bond, as the amount of carbonate bond increases, the viscosity increases and the compatibility with ink deteriorates. Therefore, pentamethylene carbonate diol or hexamethylene carbonate diol, which have a branched chain that suppresses the hydrogen bond strength of the carbonate bond, are particularly preferred.
[0080] As the (e) urethane (meth)acrylate, one that satisfies any one of the following characteristics (1) to (6) can be preferably used. (1) A compound having at least a urethane structure obtained from a polyisocyanate having an aromatic ring structure or an alicyclic structure, and an ester structure obtained from a carboxylic acid. (2) A compound having at least a urethane bond structure obtained from a diisocyanate having an alicyclic structure and an ester structure obtained from adipic acid or isophthalic acid. (3) A compound having a urethane structure obtained from a polyisocyanate having at least an aromatic ring structure or an alicyclic structure, and a carbonate structure consisting of a carbonate dipolyol. (4) A compound having a urethane structure obtained from a diisocyanate having at least an alicyclic structure, and a carbonate structure selected from at least one selected from polypentamethylene carbonate diol and polyhexamethylene carbonate diol. (5) A compound having a urethane structure and an acrylic group, which is obtained by reacting a hydroxyl group-containing acrylic ester with an isocyanate compound. (6) A compound having a urethane structure and an acrylic group, which is obtained by reacting pentaerythritol triacrylate with a diisocyanate compound having an aromatic ring structure.
[0081] (e) The weight-average molecular weight of the urethane (meth)acrylate is preferably 100 or more since the hot water resistance of the ink can be improved, and since the soft segment ratio of the polyol component in one molecule is more than a certain level, the coating film can be given flexibility and the adhesion can be improved, so the weight-average molecular weight is more preferably 300 or more, even more preferably 500 or more, even more preferably 800 or more, even more preferably 1,000 or more, and even more preferably 1,500 or more. In addition, by maintaining compatibility with the ink, the fluidity of the ink can be maintained, and good coating film appearance (leveling property) and background stain resistance can be obtained during printing, so the weight-average molecular weight is preferably 10,000 or less, more preferably 7,000 or less, and even more preferably 5,000 or less. The weight-average molecular weight of the resin can be calculated by measuring it in terms of polystyrene using gel permeation chromatography (GPC).
[0082] The content of (e) urethane (meth)acrylate in the total amount of ink is preferably 1% by mass or more, more preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 7% by mass or more in order to obtain good adhesion. In addition, by making it 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less, good compatibility with the resin can be maintained. This suppresses the increase in tackiness of the ink, and allows a printed matter with good positional accuracy of the pattern to be obtained. In addition, since the ink fluidity can be appropriately maintained, it is preferable because a printed matter with good leveling properties and no background staining can be obtained.
[0083] The ink used in the present invention preferably contains a photopolymerization initiator, particularly when the ink is cured by ultraviolet light, and may also contain a sensitizer to aid the effect of the photopolymerization initiator.
[0084] As the photopolymerization initiator, generally, α-aminoalkylphenone initiator and thioxanthone initiator are mentioned, but it is preferable to include an acylphosphine oxide compound in addition to them. Since the acylphosphine oxide compound absorbs light in the long wavelength region of 350 nm or more, it has high sensitivity even in a system containing a pigment that absorbs or reflects ultraviolet light. In addition, the acylphosphine oxide compound has a photobleaching effect that disappears from light absorption after reacting once, and due to this effect, it shows excellent internal curing properties.
[0085] Specific examples of α-aminoalkylphenone initiators include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-dimethylamino-2-(4-methyl-benzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, and 2-methyl-1-[-4(methylthio)phenyl]-2-morpholinopropan-one. These may be used alone or in combination. These polymerization initiators are preferred from the viewpoint of easy availability.
[0086] Examples of thioxanthone initiators include 2,4-diethylthioxanthone, 2-isopropylthioxanthone, and 2-chlorothioxanthone.
[0087] The content of the photopolymerization initiator in the ink is preferably 0.1% by mass or more relative to the total mass of the ink, since good sensitivity can be obtained. More preferably, the content is 1% by mass or more, and even more preferably, the content is 3% by mass or more. Furthermore, the content of the photopolymerization initiator is preferably 20% by mass or less, since the storage stability of the ink is improved. More preferably, the content is 15% by mass or less, and even more preferably, the content is 10% by mass or less.
[0088] Specific examples of sensitizers include 2,4-diethylthioxanthone, isopropylthioxanthone, 2,3-bis(4-diethylaminobenzal)cyclopentanone, 2,6-bis(4-dimethylaminobenzal)cyclohexanone, 2,6-bis(4-dimethylaminobenzal)-4-methylcyclohexanone, Michler's ketone, 4,4-bis(diethylamino)-benzophenone, 4,4-bis(dimethylamino)chalcone, 4,4-bis(diethylamino)chalcone, p-dimethylaminocinnamylidene indanone, p-dimethylaminobenzylidene indanone, 2-(p -dimethylaminophenylvinylene)-isonaphthothiazole, 1,3-bis(4-dimethylaminobenzal)acetone, 1,3-carbonyl-bis(4-diethylaminobenzal)acetone, 3,3-carbonyl-bis(7-diethylaminocoumarin), N-phenyl-N-ethylethanolamine, N-phenylethanolamine, N-tolyldiethanolamine, isoamyl dimethylaminobenzoate, isoamyl diethylaminobenzoate, 3-phenyl-5-benzoylthiotetrazole, and 1-phenyl-5-ethoxycarbonylthiotetrazole.
[0089] When a sensitizer is contained, the content of the sensitizer is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 3% by mass or more, of the ink in order to obtain good sensitivity of the ink, and is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, of the ink in order to improve the storage stability of the ink.
[0090] In the ink used in the present invention, one or more types of photopolymerization initiators and sensitizers can be used.
[0091] The ink used in the present invention preferably contains an emulsifier. When the ink contains an emulsifier, an appropriate amount of dampening water (generally said to be 10 to 20% by mass of the total amount of ink) is incorporated and emulsified during water-based lithographic printing, thereby increasing the repellency of non-image areas against dampening water and improving the scumming resistance of the ink.
[0092] The ink used in the present invention may contain other components as long as the effects of the present invention are not impaired.
[0093] Suitable examples of inks for use in the present invention include those described in WO 2017 / 47817 and WO 2018 / 163941. EXAMPLES
[0094] The present invention will be specifically described below with reference to examples, but the present invention should not be construed as being limited to these examples.
[0095] <Ink raw materials> Pigment: Lionol Blue FG7330 (manufactured by Toyo Color Co., Ltd.) Acrylic resin 1: 0.6 equivalents of glycidyl methacrylate was added to the carboxyl group of a copolymer consisting of 25% by mass of methyl methacrylate, 25% by mass of styrene, and 50% by mass of methacrylic acid to obtain acrylic resin 1. The obtained resin 1 had a weight average molecular weight of 34,000, an acid value of 102 mgKOH / g, and an iodine value of 2.0 mol / kg. Hydroxyl (meth)acrylate: (meth)acrylate having a hydroxyl group, a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate "Miramer" (registered trademark) M340 (manufactured by MIWON), hydroxyl value 115 mg KOH / g Aliphatic bifunctional (meth)acrylate: 1,10-decanediol diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., NK Ester A-DOD-N). Hydroxyl value: 0 mg KOH / g.
[0096] Urethane acrylate: A urethane acrylate consisting of alicyclic diisocyanate (hydrogenated XDI), carboxylic acid (isophthalic acid and adipic acid), polyol, and 2-hydroxyethyl acrylate, with a weight average molecular weight (Mw) of 3,600 and a urethane bond fraction of 8 mass%.
[0097] Photopolymerization initiator 1: 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide "Lucirin" (registered trademark) TPO (manufactured by BASF) Photopolymerization initiator 2: 2-[4-(methylthio)benzoyl]-2-(4-morpholinyl)propane "Irgacure" (registered trademark) 907 (manufactured by BASF) Sensitizer: 4,4-bis(diethylamino)benzophenone (manufactured by Hodogaya Chemical Co., Ltd.) Extender pigment: "Microace" (registered trademark) P-3 (manufactured by Nippon Talc Co., Ltd.) Polymerization inhibitor: p-methoxyphenol (Wako Pure Chemical Industries, Ltd.) Emulsifier: "Rheodol" (registered trademark) TW-L120 (Kao Corporation) HLB value 16.7 Additive: Lauryl acrylate (Wako Pure Chemical Industries, Ltd.) Wax: "KTL" (registered trademark) 4N (manufactured by Kitamura Co., Ltd.).
[0098] <Film> Film 1: Polyamide film "Bonyl Q" (manufactured by Kojin Film Co., Ltd.) A film having an easy-adhesion layer. Film thickness: 15 μm. The easy-adhesion layer is a layer containing polyurethane containing polycarbonate polyol as a diol component.
[0099] Film 2: The surface of a polyamide film "EMBLEM" (registered trademark) ON (manufactured by Unitika Ltd.) was coated with "ETERNACOLL" (registered trademark) UW5502 (manufactured by Ube Industries, Ltd., polyurethane containing polycarbonate polyol as a diol component) diluted 10 times with water. Film thickness: 15 μm.
[0100] Film 3: The surface of a polyamide film "EMBLEM" (registered trademark) ON (manufactured by Unitika Ltd.) was coated with a mixture of 100 parts by mass of "ETERNACOLL" (registered trademark) UW5502 (manufactured by Ube Industries, Ltd., polyurethane containing polycarbonate polyol as a diol component) and 1 part by mass of "SNOWTEX" (registered trademark) ST-C (manufactured by Nissan Chemical Industries, Ltd., colloidal silica, particle size 12 nm), diluted 10 times with water. Film thickness 15 μm.
[0101] Film 4: The surface of a polyamide film "EMBLEM" (registered trademark) ON (manufactured by Unitika Ltd.) was coated with a mixture of 100 parts by mass of "ETERNACOLL" (registered trademark) UW5502 (manufactured by Ube Industries, Ltd., polyurethane containing polycarbonate polyol as a diol component) and 5 parts by mass of "SNOWTEX" (registered trademark) ST-C (manufactured by Nissan Chemical Industries, Ltd., colloidal silica, particle size 12 nm), diluted 10 times with water. Film thickness 15 μm.
[0102] Film 5: The surface of a polyamide film "EMBLEM" (registered trademark) ON (manufactured by Unitika Ltd.) was coated with "ETERNACOLL" (registered trademark) UW5002E (manufactured by Ube Industries, Ltd., polyurethane containing polycarbonate polyol as a diol component) diluted 10 times with water. Film thickness: 15 μm.
[0103] Film 6: The surface of a polyamide film "EMBLEM" (registered trademark) ON (manufactured by Unitika Ltd.) was coated with "ETERNACOLL" (registered trademark) UW3018 (manufactured by Ube Industries, Ltd., polyurethane containing polycarbonate polyol as a diol component) diluted 10 times with water. Film thickness: 15 μm.
[0104] Film 7: The surface of a polyamide film "EMBLEM" (registered trademark) ON (manufactured by Unitika Ltd.) was coated with "ELASTRON" (registered trademark) H38 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., polyurethane containing polyether polyol as a diol component) diluted 10 times with water. Film thickness: 15 μm.
[0105] Film 8: The surface of a polyamide film "EMBLEM" (registered trademark) ON (manufactured by Unitika Ltd.) was coated with "ELASTRON" (registered trademark) E37 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., polyurethane containing polyester polyol as a diol component) diluted 10 times with water. Film thickness: 15 μm.
[0106] <Measurement of the amount of radicals present on the surface of the film> Using an electron spin resonance (ESR) device ELEXSSYS E580 (manufactured by BRUKER), the amount of radicals present on the film surface after irradiation with 30 kGy of electron beam was measured. The film sample irradiated with electron beam was stored in a low temperature atmosphere using dry ice immediately after irradiation, and the temperature was returned to room temperature just before the measurement of the amount of radicals. The detailed conditions are as follows.
[0107] Measurement temperature: room temperature Central magnetic field: Around 3368G Magnetic field sweep range: 400G Modulation: 100kHz, 2G Microwave: 9.44GHz, 0.1mW Sweep time: 83.89s x 4times Time constant: 163.84ms Number of data points: 1024 points Cavity: Super-High-Q Table 1 shows the measurement results of the radical amount.
[0108] <FT-IR-ATR measurement of film surface> The surface of the film 1 having the easy-adhesion layer and the coating surface of the films 2 to 8 were measured by the attenuated total reflection (ATR) method using an FT-IR (Bio-Rad Digilab's "FTS-55A"). -1 The area of the peak present in the range of 1720 to 1760 cm is taken as the peak intensity ν1 of the stretching vibration of the nitrogen-hydrogen single bond. -1 The area of the peak present at 1510 cm was used as the peak intensity ν2 of the stretching vibration of the carbon-oxygen double bond, and ν1 / ν2 was calculated. -1 value and 1550cm -1 A straight line was drawn connecting the values of 1510cm and this was used as the baseline. -1 ~1550cm -1 The area enclosed by this baseline and the spectrum obtained in the range was calculated as ν1. Similarly, to calculate ν2, -1 value and 1760 cm -1 Draw a line connecting the values of 1720~1760cm -1 The area enclosed by this baseline and the spectrum obtained in the range was calculated as ν2. Table 1 shows the evaluation results of ν1 / ν2.
[0109] <Measurement of surface roughness Ra of film coating surface> The surface roughness Ra of the surface of film 1 having the easy-adhesion layer and the coating surfaces of films 2 to 8 was measured using an atomic force microscope Dimension FastScan (manufactured by BRUKER) in accordance with JIS R 1683:2007, standard name: Method for measuring surface roughness of fine ceramic thin films using an atomic force microscope. Table 1 shows the measurement results of Ra.
[0110] <Waterless lithographic printing test> A waterless lithographic printing plate (TAN-E, Toray Industries, Inc.) was attached to an offset printing machine (Oliver 266EPZ, Sakurai Graphic Systems Co., Ltd.), and the inks having the compositions shown in Examples 1 to 4, 6 to 10, and Comparative Examples 1 and 2 were used to print on a film, to obtain prints.
[0111] <Water-based lithographic printing test> A waterless lithographic printing plate (XP-F, Fuji Film Corporation) was attached to an offset printing press (Oliver 266EPZ, Sakurai Graphic Systems Co., Ltd.), and the film was printed using tap water mixed with 3% by weight of an etching solution (SOLAIA-505, T&K TOKA Corporation) as the dampening water and the ink of Example 5 to obtain a print.
[0112] <Electron beam irradiation conditions> The ink was cured using an electron beam irradiation device (LB1036, manufactured by I-Electron Beam Co., Ltd.) under conditions of an acceleration voltage of 110 kV, a beam current of 5.0 mA, and an absorbed dose of 30 kGy to produce a printed material.
[0113] <UV irradiation conditions> The ink was cured using an ultraviolet irradiation device (USHIO Corporation, 120 W / cm, one ultra-high pressure metal halide lamp) at a belt conveyor speed of 50 m / min to produce a print.
[0114] <Evaluation of ink transfer> Using the active energy ray curable lithographic printing inks described in the Examples and Comparative Examples, 1,000 m of each film described in Table 2 was printed in a waterless lithographic printing test (Examples 1-4, 6-10, Comparative Examples 1-2) or a water-based lithographic printing test (Example 5) at a printing speed of 200 m / min and an active energy ray curable lithographic printing ink supply rate of 50%, and then the ink was cured using electron beams or ultraviolet rays to produce a printed product. The density of the solid area was evaluated using a reflection densitometer (SpectroEye, Status E, manufactured by GretagMacbeth) with high-quality paper as the paper white (reflection density 0 as a reference). It was determined that the higher the value of the ink transferability, the better the ink transferability.
[0115] <Peel strength> The peel strength test and evaluation criteria for the printed matter on the film were performed in accordance with the standard number JIS K 6854-2:1999, standard name Adhesives-Test method for peel adhesion strength-Part 2: 180 degree peeling. Using the active energy ray curable lithographic printing inks described in the Examples and Comparative Examples, 1,000 m of printing was performed on each film described in Table 2 at a printing speed of 200 m / min and an active energy ray curable lithographic printing ink supply rate of 50%, in a waterless lithographic printing test (Examples 1 to 4, 6 to 10, Comparative Examples 1 to 2) or a water-containing lithographic printing test (Example 5). The ink was then cured using electron beams or ultraviolet rays to produce a printed matter. A two-component adhesive (LX-500 / KR-90S: manufactured by DIC Corporation) was applied to the surface of the printed matter at a rate of 3.5 g / m. 2 After laminating the film, the print was placed in an oven and left at 60°C for a day to harden, producing a peel strength evaluation sample. Some of the peel strength evaluation samples were also immersed in 100°C hot water for 30 minutes to produce a post-boiling peel strength evaluation sample. These samples were cut into 15mm widths with a cutter, and the peel strength between the print and the film was measured. For the measurement, a tensile tester was used to perform a 180-degree peel test at a load speed of 100mm / min.
[0116] When the peel strength was less than 1 N / 15 mm, the adhesion was judged to be extremely insufficient, when it was 1 N / 15 mm or more and less than 3 N / 15 mm, the adhesion was judged to be insufficient, when it was 3 N / 15 mm or more and 5 N / 15 mm, the adhesion was judged to be good, and when it was 5 N / 15 mm or more, the adhesion was judged to be extremely good.
[0117] [Example 1] Each component was weighed according to the ink composition shown in Table 2, and the ink was obtained by passing it three times at a gap of 1 using a three-roll mill "EXAKT" (registered trademark) M-80S (manufactured by EXAKT). The ink thus prepared was printed on film 1 by a waterless lithographic printing method, and cured with an electron beam irradiation device to produce a print. The ink transferability was good at 1.60. The peel strength was 5.7 N / 15 mm, and the adhesion was extremely good. In addition, the peel strength after boiling was also 5.8 N / 15 mm, and the adhesion after boiling was also extremely good.
[0118] [Example 2] Each component was weighed according to the ink composition shown in Table 2, and the ink was obtained by passing it three times at a gap of 1 using a three-roll mill "EXAKT" (registered trademark) M-80S (manufactured by EXAKT). The ink thus prepared was printed on film 1 by a waterless lithographic printing method, and cured with an electron beam irradiation device to prepare a print. The ink transferability was 1.75, which was extremely good. The peel strength was 6.4 N / 15 mm, and the adhesion was extremely good. In addition, the peel strength after boiling was also 6.6 N / 15 mm, and the adhesion after boiling was also extremely good.
[0119] [Example 3] Each component was weighed according to the ink composition shown in Table 2, and the ink was obtained by passing it three times at a gap of 1 using a three-roll mill "EXAKT" (registered trademark) M-80S (manufactured by EXAKT). The ink thus prepared was printed on film 1 by a waterless lithographic printing method, and cured with an electron beam irradiation device to prepare a print. The ink transferability was 1.72, which was extremely good. The peel strength was 8.1 N / 15 mm, and the adhesion was extremely good. In addition, the peel strength after boiling was also 8.5 N / 15 mm, and the adhesion after boiling was also extremely good.
[0120] [ Reference example 1 ] Each component was weighed according to the ink composition shown in Table 2, and the ink was obtained by passing it three times at a gap of 1 using a three-roll mill "EXAKT" (registered trademark) M-80S (manufactured by EXAKT). The ink thus prepared was printed on film 1 by a waterless lithographic printing method, and cured with an ultraviolet irradiation device to produce a printed matter. The ink transferability was good at 1.60. The peel strength was 4.6 N / 15 mm, and the adhesion was good. In addition, the peel strength after boiling was also 4.4 N / 15 mm, and the adhesion after boiling was also good.
[0121] [Example 5] Each component was weighed according to the ink composition shown in Table 2, and the ink was obtained by passing it three times at a gap of 1 using a three-roll mill "EXAKT" (registered trademark) M-80S (manufactured by EXAKT). The ink thus prepared was printed on film 1 using a water-based lithographic printing method, and cured with an electron beam irradiation device to produce a print. The ink transferability was good at 1.55. The peel strength was 3.5 N / 15 mm, and the adhesion was good. In addition, the peel strength after boiling was also 3.3 N / 15 mm, and the adhesion after boiling was also good.
[0122] [Examples 6 to 8] Printing experiments were carried out in the same manner as in Example 1, except that the type of film was changed to Film 2 (Example 6), Film 3 (Example 7), and Film 4 (Example 8), and the ink transferability and adhesion to the film were evaluated. The ink transferability was good, at 1.60 for all cases. The peel strength was 4.8 N / 15 mm in Example 6, and the adhesion was good. In Examples 7 and 8, the peel strength was 5.1 N / 15 mm and 6.1 N / 15 mm, respectively, and the adhesion was very good. In addition, the peel strength after boiling was 4.5 N / 15 mm in Example 6, and the adhesion after boiling was also good. In Examples 7 and 8, the peel strength was 5.2 N / 15 mm and 5.9 N / 15 mm, and the adhesion after boiling was also very good.
[0123] [Examples 9 to 10] A printing experiment was carried out in the same manner as in Example 1, except that the type of film was changed to Film 5 (Example 9) and Film 6 (Example 10), and the ink transferability and adhesion to the film were evaluated. The ink transferability was good at 1.60 in both cases. The peel strength was 6.1 N / 15 mm in Example 9, and the adhesion was very good. The adhesion was good at 4.4 N / 15 mm in Example 10. The peel strength after boiling was 4.7 N / 15 mm in Example 9 and 4.6 N / 15 mm in Example 10, and the adhesion after boiling was also good.
[0124] [Comparative Example 1] A printing experiment was carried out in the same manner as in Example 1, except that the type of film was changed to Film 7, and the ink transferability and adhesion to the film were evaluated. The ink transferability was good at 1.60. The peel strength was 4.2 N / 15 mm, and the adhesion was good. However, the peel strength after boiling was 1.6 N / 15 mm, and the adhesion after boiling was insufficient.
[0125] [Comparative Example 2] A printing experiment was carried out in the same manner as in Example 1, except that the type of film was changed to Film 8, and the ink transferability and adhesion to the film were evaluated. The ink transferability was good at 1.60. The peel strength was 4.6 N / 15 mm, and the adhesion was good. However, the peel strength after boiling was 1.9 N / 15 mm, and the adhesion after boiling was insufficient.
[0126] [Table 1]
[0127] [Table 1] [Explanation of symbols]
[0128] 1 Ink roller 2 Lithographic printing plate 3 Plate cylinder 4. Blanket 5. Film 6 Support Rollers
Claims
1. A method for producing a printed matter, comprising the steps of printing an electron beam curable ink on a film and irradiating an electron beam onto the surface on which the ink has been printed, the method comprising the steps of: printing an electron beam curable ink on a film; ... irradiating an electron beam of 30 kGy onto the surface on which the polyurethane-containing layer is formed, the method comprising the steps of: irradiating an electron beam of 30 kGy onto the surface on which the polyurethane-containing layer is formed, the method comprising the steps of: irradiating an electron beam of 30 kGy onto the surface on which the polyurethane-containing layer is formed, the method comprising the steps of: 18 the ink is printed on a layer containing a polyurethane in which the polycarbonate polyol is used as a polyol component.
2. The method for producing a printed matter according to claim 1, wherein the film has a surface roughness Ra of 5 to 30 nm on the surface on which the layer containing polyurethane in which polycarbonate polyol is used as a polyol component is provided.
3. The method for producing a printed matter according to claim 1 or 2, characterized in that the film has a ratio of a peak intensity v1 of a stretching vibration of a carbon-nitrogen single bond to a peak intensity v2 of a stretching vibration of a carbon-oxygen double bond, v1 / v2, within a range of 1 to 2, as determined by an FT-IR-ATR method in a measurement from the surface of a layer containing polyurethane in which polycarbonate polyol is used as a polyol component.
4. The method for producing a printed matter according to any one of claims 1 to 3, wherein the thickness of the film is 10 µm or more and 30 µm or less.
5. The method for producing a printed matter according to any one of claims 1 to 4, wherein the ink used is an active energy ray-curable ink containing (a) an acrylic resin having an acid value of 30 mgKOH / g or more and 250 mgKOH / g or less.
6. 6. The method for producing a printed matter according to claim 5, wherein the acrylic resin is an acrylic resin having an ethylenically unsaturated group, and the ink contains (b) a pigment, and (c) a (meth)acrylate having a hydroxyl group.
7. The method for producing a printed matter according to claim 5 or 6, wherein the ink further contains (d) a bifunctional (meth)acrylate having a chain aliphatic skeleton having from 8 to 18 carbon atoms.
8. The method for producing a printed matter according to any one of claims 5 to 7, wherein the ink further contains (e) a urethane (meth)acrylate.
9. 9. The method for producing a printed matter according to claim 1, wherein the step of printing the ink onto the film is carried out using a waterless planographic printing plate.
10. A laminate comprising a polyamide film layer and a layer containing polyurethane in which polycarbonate polyol is used as a polyol component as an outermost layer on at least one surface of the film, the layer containing polyurethane in which polycarbonate polyol is used as a polyol component being laminated with a cured product of an electron beam curable printing ink, the film being irradiated with an electron beam of 30 kGy from the surface on which the layer containing polyurethane is provided, and the amount of radicals present in the surface layer of the film being 2×10 18 The laminate has a density of 1 / g or more.
Citation Information
Patent Citations
Printing ink binder and printing ink
JP2001151847A
Composition for coating and laminated film
JP2011094125A
Active energy ray-curable ink composition for offset printing and production method of printed matter using the same
JP2015168730A
Active energy ray-curable printing ink and method of manufacturing printed matter
JP2019059850A
Emulsion composition
JP2019081887A